Maternal Secure Base Scripts’ socio demographic predictive variables - Nóblega, Magaly (2017)
This study evaluates the predictive capacity of sociodemographic variables of the mother over the level of maternal secure base scripts. The participants were 83 mothers from 15 to 45 years old (M = 24.72, SD = 8.70).The level of maternal secure base was evaluated through the Narratives of Adult Attachment (Waters & Waters, 2006). The results show that the participants do not have an adequate level of secure base script. It was found that interaction between the age of the mother and the educational attainment level, partly explains the level of the maternal secure base script (R2 = .19). The protector role of the level of educational attainment for older mothers to have a higher level of secure base scripts isproposed.